Novel investigational therapies for treating biliary tract carcinoma. (1st December 2016) - Tampellini, M.; La Salvia, A.; Scagliotti, G. V.
ABSTRACT: Introduction: Cholangiocarcinoma (CCA) is an epithelial cell malignancy arising from bile ducts and/or peribiliary glands. Even though it is considered as a rare neoplasm, its incidence is raising, particularly in developed countries. Prognosis is generally poor with few patients who present the inclusion criteria for surgery (the mainstay treatment for this tumour). Several genetic alterations potentially driving tumour progression have been described, representing a possible target for new compounds. Areas covered: A clinical trial search in Clinicaltrials.gov encompassing a literature search in PubMed and ASCO/ESMO Websites was undertaken in March 2016. Expert opinion: Notwithstanding a large number of drug tested, results are still disappointing. The main reasons could be the low number of patients enrolled in trials, and the lack of a patient selection based on the biological profile of the tumours. Potential active drugs could have been discharged simply because beneficial in a particular subgroup of patients and not in un unselected population. The future direction of the research should consider biomarker evaluation in order to describe the genetic alteration/s that drive tumour progression and aggressiveness and the mechanisms of drug resistance. Finally, it will be of great interest to consider the results of immunotherapy whenever available.